1996
DOI: 10.1212/wnl.46.6.1530
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of patients with epileptic and nonepileptic seizures

Abstract: Epileptic seizures (ES) and nonepileptic seizures (NES) often coexist in patients with treatment-refractory seizures. There are few data on ictal features of these different seizure types in the same patient. We identified 20 patients with ES from a group of 99 NES patients (ES/NES) and compared this group with patients with only ES or NES. All 20 ES/NES patients developed NES after ES. Clinical features of NES clearly differed from ES in 18 of 20 cases. In patients with ES/NES their ES were similar to seizure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
78
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(88 citation statements)
references
References 7 publications
9
78
0
1
Order By: Relevance
“…The clinical feature of NES are varied (1)(2)(3)(4)(5), and the clinical diagnosis is frequently difficult and requires experience in recognizing the typical symptoms of NES and differentiating them from epilepsy. LVEM is critical for the diagnosis in difficult cases and, when there is doubt about the nature of the events, prolonged and multiple LVEM studies are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical feature of NES are varied (1)(2)(3)(4)(5), and the clinical diagnosis is frequently difficult and requires experience in recognizing the typical symptoms of NES and differentiating them from epilepsy. LVEM is critical for the diagnosis in difficult cases and, when there is doubt about the nature of the events, prolonged and multiple LVEM studies are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…On completion of PVEM, we divided patients into four groups: definite PNESs, possible PNESs, possible epilepsy, and definite epilepsy. As previously, we used the following criteria: definite PNESs is defined as habitual spells recorded on video-EEG without an ictal EEG discharge and normal background alpha rhythm during the events; possible PNESs is defined as no events recorded and continuously normal interictal EEGs; possible epilepsy is defined as no events recorded with interictal epileptiform discharges; definite epilepsy is defined as recorded stereotypic events with an ictal EEG discharge (17,18,20,29). Only the data on patients with definite PNESs and definite epilepsy were used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of PNES research has focused on the clinical characteristics of PNESs or on predicting the diagnosis based on MMPI and clinical history data (16,(27)(28)(29). Other studies evaluated the association between PNESs and psychological or sexual trauma or other psychiatric comorbities (30,31), outcome after the diagnosis of PNESs (13,(24)(25)(26), or the incidence of PNESs (20,21).…”
mentioning
confidence: 99%
“…Although previous studies have reported a high prevalence (5%-50%) of ES in PNES patients (PNES/ES) (Sigurdardottir and Olafsson, 1998;Benbadis et al, 2001;Martin et al, 2003), few authors investigated PNES and PNES/ES patients separately to determine the possible influence of this comorbidity on psychological and clinical aspects (Devinsky et al, 1996;Owczarek and Jederzejczak, 2001;Reuber et al, 2002;Kuyk et al, 2003;Galimberti et al, 2003).…”
mentioning
confidence: 99%